Idiopathic toe walking and sensory processing dysfunction - Williams, Cylie M (BioMed Central, 2010)
BACKGROUND: It is generally understood that toe walking involves the absence or limitation of heel strike in the contact phase of the gait cycle. Toe walking has been identified as a symptom of disease processes, trauma and/or neurogenic influences. When there is no obvious cause of the gait pattern, a diagnosis of idiopathic toe walking (ITW) is made. Although there has been limited research into the pathophysiology of ITW, there has been an increasing number of contemporary texts and practitioner debates proposing that this gait pattern is linked to a sensory processing dysfunction (SPD). The purpose of this paper is to examine the literature and provide a summary of what is known about the relationship between toe walking and SPD. METHOD: Forty-nine articles were reviewed, predominantly sourced from peer reviewed journals. Five contemporary texts were also reviewed. The literature styles consisted of author opinion pieces, letters to the editor, clinical trials, case studies, classification studies, poster/conference abstracts and narrative literature reviews. Literature was assessed and graded according to level of evidence. RESULTS: Only one small prospective, descriptive study without control has been conducted in relation to idiopathic toe walking and sensory processing. A cross-sectional study into the prevalence of idiopathic toe walking proposed sensory processing as being a reason for the difference. A proposed link between ITW and sensory processing was found within four contemporary texts and one conference abstract. CONCLUSION: Based on the limited conclusive evidence available, the relationship between ITW and sensory processing has not been confirmed. Given the limited number and types of studies together with the growing body of anecdotal evidence it is proposed that further investigation of this relationship would be advantageous.